Optical Coherence Tomography Angiography: Investigating Vessel Density Changes Induced by Caffeine in Healthy Subjects - Mitchell Jacobs; Nicholas Demas; Angela Hemesath; Christopher Turski; Nicholas Fowler; John Benjamin Chadwell; Alec Dupont; Victoria Kupper; Kishor Acharya; Sarah Robbins; Kory Heier; Ramiro Maldonado (Journal of Ophthalmology)
Conclusion: In conclusion, 200 mg of caffeine elevated blood pressure after 2 h but did not impact the retinal VD. This underscores the intricate relationship between caffeine, blood pressure, and retinal vascular dynamics, prompting further exploration of their implications for ocular health, especially in subjects with vascular disease.